Proposal of a marbofloxacin dose to treat infections associated to Escherichia coli in 3-week-old kids (FAVE Sección Ciencias Veterinarias, 2019)
A dose of marbofloxacin (MFX) to treat gastrointestinal infections caused by Escherichia coli in 3-week-old kids was estimated. The pharmacodynamics of MFX against E. coli was evaluated in vitro by estimation of mínimum inhibitory concentration (MIC), mínimum bactericide concentration (MBC) and mutant prevention concentration (MPC). Marbofloxacin was administered to 3-week -old kids by subcutaneous route at the dose of 2 mg/kg. The pharmacokinetic parameters were estimated by non-compartmental analysis. The dose of MFX capable to protect the 95% of population was calculated considering the population distribution of pharmacokinetic parameters. The efficacy of MFX was evaluated by the relationship between the area under curve and MPC (AUC/MPC) with a cut-off value of 22 h. The results showed that the estimated dose of MFX to reach the clinical outcome of gastrointestinal infections caused by E. coli and to prevent the bacterial resistance at the 95% of the population of 3-week-old kids was 3.179 mg/kg, which for practical reasons was fixed at 3.5 mg/kg.
Keywords: marbofloxacin; Escherichia coli; goats